Risk of developing congenital malformations in infants whose mothers live under unfavourable geochemical conditions - Vlasova, Olena (Journal of Education, Health and Sport, 2018)
Abstract. The objective of the paper was to determine the risk of congenital malformations in children whose mothers lived in areas with different geochemical characteristics. Material and methods. We have analysed 492 protocols of autopsy on newborn infants and fetuses, which died in the uterus or after birth during 2004-2014 in Chernivtsi due to the geochemical disadvantages of the places where the pregnant women lived. Results. When pregnant women live in the areas with a chronic exposition to heavy metals the risk of the fetal death and that of newborn infants increases by 6,1 times compared to conditionally clean areas. It has been established that in the structure of birth defects in deceased children, whose mothers lived in places of geochemical disadvantage, there was a reliable risk of congenital heart disease and of multiple congenital malformations. Conclusions. The peculiarities of the distribution of incidence of congenital malformations in ecologically unfavorable areas are: the prevalence of congenital heart disease (OR = 2.13 (95DI 1.05-4.31), multiple congenital heart diseases OR = 1.8 (95CI 1.1- 2.8), especially in the male population (OR = 2.7 (95CI 1.04-7.4).